Under‐Ice Population Density Estimation of Alaska Blackfish. (10th April 2018) - Fraley, Kevin M.; Haynes, Trevor B.; López, J. Andrés
Abstract: The Alaska Blackfish Dallia pectoralis is an understudied but ecologically important mudminnow occurring in lentic ecosystems of subarctic and Arctic Alaska. We sampled a population of Alaska Blackfish during the winter months in an upland pond near Fairbanks, Alaska, and we used a simple mark–recapture estimator to provide the first population estimate for this species. We found that Alaska Blackfish density in the pond was approximately 0.27 individuals/m 2, equating to an estimated biomass of 15 g/m 2 of pond surface area, which is similar to density estimates reported for other mudminnow species. We tested capture methods and found that under‐ice minnow trapping was a poor method during early winter (September–December) but was highly effective near methane sumps and areas of high muskrat Ondatra zibethicus activity in late winter (March–April). Qualitatively, nearshore minnow trapping, seining, and kicknetting during the ice‐free season were less effective than under‐ice trapping. Cursorily, pelvic fin clips were more effective for batch marking of Alaska Blackfish than two types of subcutaneous tags, given the high numbers of individuals we captured and the species' relatively small body size and dark skin, which hindered tag visualization. We demonstrated that Alaska Blackfish can occur at high densities in their typical habitat, underscoring their importance as forage fish in Alaskan freshwater ecosystems that support subsistence and sport fisheries for piscivorous fishes. Extending this approach across the geographic range of Alaska Blackfish will improve understanding of the ecological role of this species in the varying aquatic ecosystems where it occurs.